Supporting the journey of architecture students towards graduation through a design ePortfolio - Colabella, Sofia; Pugnale, Alberto; Mack, Michael; Woo, Catherine Mei Min (Frontiers in Education, 2023)
This paper presents the different steps of the journey that led to the development and implementation of a design ePortfolio as part of the “Architecture Major” of the “Bachelor of Design” (BDes) at The University of Melbourne, Australia. This design ePortfolio was developed over two years through interviews, focus groups with students, and the development of exercises and assignment guidelines. The implementation took place in different phases, starting with the introduction of four thematic exercises in the Capstone Architecture Design Studio of the BDes, and then, more broadly, at the curriculum level, with similar activities that prepared the students to already start developing a reflective journal from the first year of their studies. The objective of this research has been to explore the potential of integrating a design ePortfolio with traditional design portfolios on the curricular activities of an undergraduate architecture degree to prioritise the students’ reflections on their personal qualities, growth, career trajectory and goals, as well as on the relationship between curricular and extracurricular activities rather than those of a conventional design portfolio, which tend to be focused more on showcasing skills and competencies. The results of this two-year project illustrate the potential of such a teaching/learning tool to link the personal and professional interests and achievements of students holistically, therefore highlighting the relationship between curricular and extracurricular activities, as well as indirect connections between design studios and seminar-based subjects, that is, history and architectural technology subjects. So far, our design ePortfolio has been successfully used to encourage architecture students to reframe problems through a different lens and, as a key to creativity, to distinguish themselves from the homogeneity of students the university produces through its degree structure and modes of operation. The significance of this teaching and learning project lies in the identification of patterns in the curricular and extracurricular experiences of students that helps them define their identity, goals, and purpose. For this reason, this research has the potential of being linked to the University’s “Student Life” project, which is related to academic advice, personal growth, mentorship and the well-being of students.